2021
DOI: 10.1007/s40618-021-01566-9
|View full text |Cite
|
Sign up to set email alerts
|

Retrospective analysis of vitamin D status on ınflammatory markers and course of the disease in patients with COVID-19 infection

Abstract: Purpose The aim of the study was to investigate the association between serum 25-hydroxyvitamin D status within the last 6 months prior to COVID-19 infection and parameters of immune function and clinical outcomes. Methods Fifty-six patients, who were admitted to the emergency clinic and diagnosed with COVID–19 infection, were included in the study. Data on clinical characteristics, inflammatory parameters and vitamin D status were recorded for each patient. All the par… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
9
0
6

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(15 citation statements)
references
References 44 publications
0
9
0
6
Order By: Relevance
“…In the patients that received 60,000 IU of daily supplemental vitamin D for eight days, levels of C-reactive protein, lactase dehydrogenase, IL-6, ferritin, as well as neutrophil to lymphocyte ratios showed significant improvement compared to patients receiving no supplements. This was corroborated by a retrospective cohort study where COVID-19 patients with vitamin D deficiency had significantly lower haemoglobin and lymphocyte counts and higher levels of inflammatory markers, including C-reactive protein [ 120 ]. In addition, vitamin D deficient patients tended to require oxygen therapy and patients who had not corrected their vitamin D levels six months prior to SARS-CoV-2 infection were more likely to be diagnosed with pneumonia [ 120 ].…”
Section: Vitamin D and Covid-19: Summary Of The Evidencementioning
confidence: 81%
See 1 more Smart Citation
“…In the patients that received 60,000 IU of daily supplemental vitamin D for eight days, levels of C-reactive protein, lactase dehydrogenase, IL-6, ferritin, as well as neutrophil to lymphocyte ratios showed significant improvement compared to patients receiving no supplements. This was corroborated by a retrospective cohort study where COVID-19 patients with vitamin D deficiency had significantly lower haemoglobin and lymphocyte counts and higher levels of inflammatory markers, including C-reactive protein [ 120 ]. In addition, vitamin D deficient patients tended to require oxygen therapy and patients who had not corrected their vitamin D levels six months prior to SARS-CoV-2 infection were more likely to be diagnosed with pneumonia [ 120 ].…”
Section: Vitamin D and Covid-19: Summary Of The Evidencementioning
confidence: 81%
“…This was corroborated by a retrospective cohort study where COVID-19 patients with vitamin D deficiency had significantly lower haemoglobin and lymphocyte counts and higher levels of inflammatory markers, including C-reactive protein [ 120 ]. In addition, vitamin D deficient patients tended to require oxygen therapy and patients who had not corrected their vitamin D levels six months prior to SARS-CoV-2 infection were more likely to be diagnosed with pneumonia [ 120 ]. A randomised controlled trial (RCT) in Spain [ 121 ] investigated the effects of hydroxychloroquine and azithromycin in combination with oral calcifediol in the treatment of COVID-19.…”
Section: Vitamin D and Covid-19: Summary Of The Evidencementioning
confidence: 81%
“…In a study involving 56 patients admitted with COVID-19, in which all participants had data on 25(OH)D3 status in the 6 months prior to COVID-19 infection, it was found lower lymphocyte counts and higher C-reactive protein levels in patients with vitamin D deficiency (<20 ng/mL). In addition, the vitamin D status of patients requiring oxygen therapy was found to be lower than those not requiring oxygen therapy, and even patients un-supplemented with vitamin D in the 6 months prior to COVID-19 infection were more likely to be diagnosed with pneumonia [ 75 ]. In this line, Baktash et al .…”
Section: Observational Studiesmentioning
confidence: 99%
“…In addition, vitamin D deficiency correlated with a higher inflammatory status which, together with comorbidity burden, negatively influenced the length of hospital stay. Ünsal et al, 2021,Turkey [ 75 ] Retrospective cohort study 56 Significantly lower lymphocyte counts and higher levels of inflammatory markers were found in patients with COVID-19 and vitamin D deficiency. Panagiotou et al, 2020, UK [ 77 ] Retrospective cohort study 134 When comparing patients who required admission to ICU versus those who were treated in medical wards, a higher prevalence of vitamin D deficiency was observed in the former.…”
Section: Observational Studiesmentioning
confidence: 99%
“…i s i o n a l l y A c c e p t e d f o r P u b l i c a t i o n and that serum levels of 25(OH)D should be maintained within the range of 40-60ng/mL to minimise the risk and severity of COVID-19.²º A study conducted in patients with COVID-19 reported a more frequent occurrence of pneumonia in patients without vitamin D supplementation 6 months before diagnosing COVID-19 26. The present study could not find a relationship between vitamin D supplementation and the disease.In the present study, the mean vitamin D levels were low in both PCR-positive and PCRnegative cases, and no significant difference was found between the groups.…”
mentioning
confidence: 99%